Ability To Pay Dan Willingness To Pay Iuran BPJS Kesehatan Pada Pedagang Pasar Bulu Semarang Di Era Pandemi - Ririn Nurmandhani; Agnes Oktavi Maharani; Agus Perry Kusuma; Muhammad Iqbal (Dian Nuswantoro Semarang, 2023)
Market traders were included in the informal workers with the second largest proportion of 3.31 million people. The purpose of this study was to calculate the ability to pay and willingness to pay fur market traders for BPJS Health contributions during the pandemic. This type of research was descriptive through quantitative methods, there are 96 respondents to the fur market traders who were registered in the PBPU segment. Subjects were determined using Systematic Random Sampling. The results showed that most of the respondents' household income per month was classified as medium which was in the interval ? IDR 2.067.295,00 to ? IDR 5.168.237,00. The average total expenditure of household respondents was IDR 3.668.339,00. The biggest type of expenditure was non-food expenditure with an average total expenditure of IDR 1.756.523.00. The real amount of Ability To Pay (ATP) for Fur Market traders had an average value of IDR 84.792,00 per person per month. Most of the respondents (88.5%) were able to pay BPJS Health contributions. There were 11 respondents unable to pay BPJS Health contributions. Calculation of the estimated average Willingness To Pay (WTP) obtained was IDR 26.411.00. The researcher's suggestion is for BPJS Health to collaborate with the UPTD Semarang City market in the BPJS Health socialization program in order to increase the knowledge and awareness of traders about the importance of health insurance.